Robust exponential stabilization of stochastic coupled T‐S fuzzy complex networks subject to state‐dependent impulsive control. (3rd January 2023) - Cao, Zhengran; Li, Chuandong; Zhang, Xiaoyu; Yang, Xujun
Abstract: The problem of robust exponential stabilization for T‐S fuzzy stochastic dynamical networks (T‐S FSDNs) based on the state‐dependent impulsive controller is investigated in the paper. Using B‐equivalence approach, some sufficient conditions are provided such that every solution of considered systems intersects each impulsive surface exactly once. Then, combining with the inequality technique and comparison principle, some meaningful sufficient criteria are obtained to ensure the mean square stability of T‐S fuzzy stochastic dynamical networks. Compared to related results, the results obtained in the paper are low conservatism and easy to verify. Finally, two numerical simulations based on R ö o ssler's system and Lorenz system show the effectiveness of the obtained theoretical results.